Intentionality and the perceptual world - Nuccilli, Daniele (Phainomena (Ljubljana), 2025)
In the article, I investigate the role of sensation in the manifestation of the world in perceptual experience, as conceptualized through three distinct phenomenological approaches: those of Edmund Husserl, Wilhelm Schapp, and Leopold Blaustein. I begin by examining Husserl’s Göttingen lectures, reconstructing his account of the intentional structuring of the perceptual world, with particular emphasis on the immanent dimension that shapes the interpretation of sensory content. I then turn to Schapp’s theory of presentation-qua-Darstellung, highlighting his original claim that sensations themselves directly present objects to consciousness, fusing the properties of things with their appearance without requiring the interpretative intervention of an intentional act. Finally, I consider Blaustein’s position, which maintains the centrality of intentionality, but situates sensations outside of the intentional act, functioning as mediators, through which the external world is apprehended and interpreted.
Keywords: content of sensations; fenomenologija; intencionalnost; intentionality; manifestacija; manifestation; perceptual world; phenomenology; vsebina občutkov; zaznavni svet